Becoming Madam Secretary [large type] - Dray, Stephanie (Thorndike Press large print top shelf., 2024)
"Frances Perkins arrives in New York City at the turn of the century determined to make a difference. When Frances meets a young lawyer named Franklin Delano Roosevelt, she thinks he's a rich, arrogant dilettante who gets by on a handsome face and a famous name. But over the next twenty years, they will form a historic partnership that will carry them both to the White House. Frances is destined to rise in a political world dominated by men, facing down the Great Depression as FDR's most trusted lieutenant. And when vicious political attacks mount and personal tragedies threaten to derail her ambitions, she must decide what she's willing to sacrifice to save a nation"--